Enzinger & weiss's soft tissue tumors - Goldblum, John R.; Folpe, Andrew L; Weiss, Sharon W. (Philadelphia, PA : Elsevier, 2020)
"Presentation of soft tissue tumors illustrated with micrographs"--
Includes bibliographical references and index.
Keywords: Soft tissue tumors